2011
DOI: 10.1007/s12272-011-0206-0
|View full text |Cite
|
Sign up to set email alerts
|

In vitro sortase a inhibitory and antimicrobial activity of flavonoids isolated from the roots of Sophora flavescens

Abstract: A series of flavonoids (1-14) was isolated from the roots of Sophora flavescens. We evaluated their ability to inhibit both microbial growth and sortase A, an enzyme that plays a key role in cell wall protein anchoring and virulence in Staphylococcus aureus. Most prenylated flavonoids (7-13) displayed potent inhibitory activity against gram-positive and gram-negative bacteria except E. coli, with minimum inhibitory concentrations values ranging from 4.40 to 27.7 μM, and weak or no activity against fungal strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 23 publications
(27 reference statements)
0
43
0
Order By: Relevance
“…Although these studies identified both competitive and noncompetitive inhibitors (57,58), isolated compounds have not yet been shown to inhibit in vivo sortase activity in staphylococci, i.e., the cleavage of sorting signals or the assembly of surface proteins into the bacterial cell wall (54,(59)(60)(61)(62). Many of the isolated compounds diminish or block staphylococcal growth, indicating that they cannot function as selective inhibitors of S. aureus sortase (53,61,63,64). Thus, the efficacy of sortase inhibitors as antiinfective therapeutics was heretofore not demonstrated (62,65).…”
Section: Discussionmentioning
confidence: 99%
“…Although these studies identified both competitive and noncompetitive inhibitors (57,58), isolated compounds have not yet been shown to inhibit in vivo sortase activity in staphylococci, i.e., the cleavage of sorting signals or the assembly of surface proteins into the bacterial cell wall (54,(59)(60)(61)(62). Many of the isolated compounds diminish or block staphylococcal growth, indicating that they cannot function as selective inhibitors of S. aureus sortase (53,61,63,64). Thus, the efficacy of sortase inhibitors as antiinfective therapeutics was heretofore not demonstrated (62,65).…”
Section: Discussionmentioning
confidence: 99%
“…aureus , and B . subtilis with MIC values ranging from 3.1 to 12.5 μg/ml (Oh et al, ; Wan, Luo, Ren, & Kong, ). Sophoraflavanone B showed antimicrobial activity against MRSA (Mun et al, ).…”
Section: Antibacterial Activity Of Flavonoidsmentioning
confidence: 99%
“…Also, hydroxy group at 4′, 4, and 6 of A and B rings increase the activity (Figure ). For example, between compounds kuraridin ( 168 ) and THIPMC ( 115 ) with the same structure, compound 168 with only one difference (with compound 115 ) in position of OH on the B ring (2 and 4 instead of 4 and 6) showed high activity against MRSA strain (Lee et al, ; Oh et al, ).…”
Section: Structure–activity Relationshipmentioning
confidence: 99%
“…The isoquinoline alkaloid berberine chloride extracted from the Coptis chinensis rhizome, was reported as a potent inhibitor of sortase (IC 50 ¼ 8.7 mg/ml) with a moderate antibacterial activity against Gram-positive bacteria (MIC range of 50e400 mg/ml) [58]. Recently, Oh et al described a series of flavonoids isolated from the roots of Sophora flavescens that acted as S. aureus SrtA inhibitors [59]. The most active compound was kurarinol with an IC 50 value of 107 ± 6.6 mM (48.8 mg/ml) and weak antibacterial activity against S. aureus [MIC of 219 mM (99 mg/ml)].…”
Section: Natural Productsmentioning
confidence: 99%